ANALYSIS OF AGE, BODY WEIGHT AND ANTLER SPREAD OF BULL MOOSE HARVESTED IN MAINE, 1980-2009 - Andreozzi, Haley A.; Pekins, Peter J.; Kantar, Lee E. (Lakehead University, 2015)
Age, field-dressed body weight, and antler spread data collected from 11,566 harvested moose (Alces alces) were analyzed to assess whether temporal change has occurred in the physical characteristics of bull moose from 1980–2009 in Maine. The annual proportion and antler spread of trophy bulls (spread ≥ 137 cm; n = 851) were also analyzed. There was no evidence of a measurable decline in the body weight or antler spread of adult bull moose (≥1.5 years old), similar to findings in Vermont and New Hampshire in a recent >20 year temporal analysis. There was a slight increase in physical characteristics of yearlings that contrasted with the trend in New Hampshire and Vermont where it is speculated that parasitism by winter ticks (Dermacentor albipictus) reduces growth rate and recruitment by yearlings. The proportion of trophy bulls in the harvest declined proportionally ∼26% (9.3 to 6.9%) as harvest increased >2x from 1980–1987 to 2005–2009; however, the mean spread of trophy bulls declined by only 2% (P = 0.002). Additionally, there were no differences (P > 0.05) in the proportion of harvested bulls within each age class between 1980–1987 and 2005–2009, and the relatively stable proportion of mature bulls (>5 years old) in the harvest across time periods (30–44%) does not suggest selective harvest of older, trophy bulls. In the face of the declining regional population, continued monitoring of harvested moose is warranted to best manage the largest and longest harvested population in the northeastern United States.